Very low event rate and few device implants in drug-induced brugada. A seven-year experience of ajmaline challenge at a district general hospital. (19th May 2022) - Brown, S; Furniss, G; Dayer, M; Bailey, J; Kemp, J
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Patients with a drug-induced Brugada electrocardiogram (ECG) are thought to have a lower risk of sudden cardiac death than those with a spontaneous type 1 ECG. Despite having a Brugada ECG, most patients do not need an implantable cardioverter defibrillator (ICD). Purpose: To report a district general hospital experience on referral and outcomes of ajmaline challenge (AC) with medium term follow up. Methods: 92 consecutive patients (50 males, mean age 41 ±17) had an AC in a single centre from 2014-2021. High ventricular leads were used from 2015. Ajmaline (1m/kg) was administered intravenously over 10-minutes. Data were collected from the electronic health record. Results: The AC was positive in 18 (20%) patients. The yield from high leads was higher (7% vs 22%) p=0.28) but not statistically significant. There were no deaths or documented ventricular arrhythmias (VA) in AC positive patients during a median follow up of 3.2 years (1.7-4.9). The resting ECG was normal in 46.7%. A type 1 pattern had been provoked by fever or electrolyte derangements in 3.3%, type 2 pattern in 8.7% and a type 3 pattern in 5.4%. An RSR pattern (not in keeping with a BrS ECG) was seen in 26.4%. The test was stopped prematurely due to QRS widening >150ms in 1 patient. No adverse arrhythmic events occurred (table 1). In our cohort, positive AC patients were older (48y vs 37y p= 0.05) and more likely to have a type 2 (28% vs 4% p=0.007) or type 3 ECG (17% vs 3% p=0.05). Asymptomatic patients were more likely to have a normal ECG (22% vs 78% p=0.05) Of those with a positive AC, nine patients had symptoms of palpitations or syncope (table 2). A subcutaneous ICD (S-ICD) was implanted for syncope in two patients. No device therapies have occurred during a follow up of 2.5 years and 3.9 years respectively. Of those with a positive AC but asymptomatic, one S-ICD was initially implanted due to patient preference. A second S-ICD was implanted in a patient who experienced a collapse and brief seizure in the context of modest alcohol consumption. In seven positive patients (39%) and 18 negative patients (23%) an ILR was implanted. 1 episode of complete heart block was detected in an ajmaline negative patient during a median follow up of 2.7 years (1.7-3.9). There were no device related complications or adverse events. Conclusion: AC is safe with a low number of device implants and ICD shocks. The yield from ILR implants was very low. A single patient had a potentially adverse outcome after consuming alcohol, a known trigger for VA in BrS. Our findings are in keeping with contemporary evidence that suggests the risk of adverse cardiac events in drug-induced BrS is low. However, time to first ICD shock may occur after ten years or more from diagnosis so long term follow up is required.